The Spliceosome: The Ultimate RNA Chaperone and Sculptor. Issue 1 (January 2016) - Papasaikas, Panagiotis; Valcárcel, Juan
Abstract : The spliceosome, one of the most complex machineries of eukaryotic cells, removes intronic sequences from primary transcripts to generate functional messenger and long noncoding RNAs (lncRNA). Genetic, biochemical, and structural data reveal that the spliceosome is an RNA-based enzyme. Striking mechanistic and structural similarities strongly argue that pre-mRNA introns originated from self-catalytic group II ribozymes. However, in the spliceosome, protein components organize and activate the catalytic-site RNAs, and recognize and pair together splice sites at intron boundaries. The spliceosome is a dynamic, reversible, and flexible machine that chaperones small nuclear (sn) RNAs and a variety of pre-mRNA sequences into conformations that enable intron removal. This malleability likely contributes to the regulation of alternative splicing, a prevalent process contributing to cell differentiation, homeostasis, and disease. Trends: The spliceosome is a ribonucleoprotein complex that chaperones pre-mRNA and small nuclear (sn)RNAs into conformations resembling the RNA-based catalytic core of group II introns. Proteins such as pre-mRNA-processing-splicing factor 8 (Prp8) organize and regulate the activation of the RNA-based catalytic core of the spliceosome. The catalytic site is open to accommodate different intron lengths and sequences, and to interact with other cellular machineries. Spliceosomal subcomplexes recognize and pair splice-site sequences in a highly dynamic and reversible fashion. This architecture, together with iterative substrate recognition and proofreading, provide opportunities for alternative splicing regulation.